The Influence of Arm Muscle Strength And Hand-Eye Coordination on Volleyball Underhand Passing Ability as Viewed From The Motivation of Students At SMA Negeri 21 Makassar - Putri, Andi Gusti Ayu Nirmala; Ishak, Muhammad; Sahabuddin, Sahabuddin; AS, Hasbunallah; Hudain, Muh. Adnan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyse the effect of arm muscle strength and hand-eye coordination on volleyball underhand passing ability in terms of motivation in students of SMAN 21 Makassar. The research method used is path analysis with a population of volleyball extracurricular students of SMAN 21 Makassar. Sampling was carried out by purposive sampling with the following criteria: (1) volleyball extracurricular participants at SMAN 21 Makassar, (2) still actively practising, and (3) male, so that 20 students were obtained as samples. The test instruments used included arm muscle strength tests (Widiastuti, 2011), hand-eye coordination tests (Ismaryanti, 2018), motivation tests (Sugiyono, 2018), and the Brumbach forearm pass wall-volley test for underhand passing ability. The results of the study showed that: (1) there was a direct influence of arm muscle strength on motivation of 29.3%, (2) there was a direct influence of hand-eye coordination on motivation of 68.1%, (3) there was a direct influence of arm muscle strength on underarm passing ability of 28.2%, (4) there was a direct influence of hand-eye coordination on underarm passing ability of 27.4%, (5) there was a direct influence of motivation on underarm passing ability of 45.4%, (6) there was an indirect influence of arm muscle strength on underarm passing ability through motivation of 13.3%, and (7) there was an indirect influence of hand-eye coordination on underarm passing ability through motivation of 30.9%. The conclusion of this study is that arm muscle strength and hand-eye coordination contribute significantly to underarm passing ability in volleyball, both directly and indirectly through motivation, with hand-eye coordination being the dominant factor influencing students' motivation in volleyball activities.